Dual‐band branch‐line hybrid with distinct power division ratio over the two bands. Issue 1 (11th May 2012) - Rawat, Karun; Rawat, Meenakshi; Hashmi, Mohammad S.; Ghannouchi, Fadhel M.
Abstract This article presents a novel methodology for the design of transmission line‐based dual‐band branch‐line hybrid with distinct power division over any two specified frequencies. These distinct power divisions at specified frequencies are achieved while keeping the quadrature relation intact at both the frequencies. To demonstrate the effectiveness of the proposed technique, a prototype of dual‐band uneven branch‐line hybrid operating at 1960 and 3500 MHz has been designed for use in Wideband Code Division Multiple Access (WCDMA) and Worldwide Interoperability for Microwave Access (WiMax) applications. The designed hybrid possesses equal power division in the WCDMA band and 3‐dB unequal power division in the WiMax band. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2013.